Disease control in coriander and other spice seeds : - Dennis, Jeremy (Rural Industries Research and Development Corporation, 1997)
This project initially intended to include research on diseases of other spice seed crops (eg. dill, cumin, fennel, aniseed, caraway, and fenugreek). There has, however, been little commercial development of these crops and no major disease issues were indentified.